A Lagrangian formulation of a theory of a scalar field superfluid dark matter - Tema, Seturumane (Department of Mathematics and Applied Mathematics, 2023)
In this thesis we discuss the dynamics of the relativistic Lagrangian of the theory of dark matter superfluidity. The second and third chapters of the thesis are a review. In the fourth chapter we show that a complex scalar field whose dynamics are dictated by such a Lagrangian, models dust in the background universe on cosmological scale. Prior to our calculations, the theory was shown to model dust on cosmological scale and a superfluid on galactic scale in the non-relativistic case [1]. This project, extends the non-relativistic theory, to include the relativistic background. We continued, using the relativistic Lagrangian, to investigate how perturbations of such a theory grow in a perturbed universe, and found that the density contrast (of the theory) is constant when the complex scalar field is not coupled to baryons in the weak-field limit.